Satisfaction and behavioural intention of Middle Eastern tourists toward Malaysian restaurants - Sara, Safaeimehneh (2018)
Satisfaction as the heart of marketing which influences behavioural intentions of customers has been neglected regarding the exploration of fast growing Middle East tourists in Malaysian restaurants. Therefore this study intended to investigate the Middle Eastern tourists’ satisfaction and behavioural intentions toward restaurants in Malaysia as a step to cover this gap. Since satisfaction in hospitality is multidimensional and it is a combination of both products and service, multi-attribute scales are the most appropriate method for measuring customer satisfaction in this segment. The dimensions of Food, Service, Environment, and Other was chosen as independent variables base on their frequency in previous studies. Considering both regression results, which are statistical in nature, and IPA (Importance-Performance Analysis) results, which are descriptive, this study provides a more comprehensive picture for Malaysian restaurant operators. The IPA shows that Malaysian restaurants were successful in delivering serve food as ordered, accurate check, neat and well-dressed staff, cleanness of the restaurant, as most important attributes in contributing to satisfaction. Likewise serve food as ordered, operation hours, cleanness of the restaurant, and pleasing aroma in the restaurant were most important attributes in contributing to behavioural intention. The IPA results concluded that taste of food, healthiness of food, quality of the food, freshness of the food ingredient and prompt and quick service are the most important areas where Malaysian restaurateurs, can make improvements to satisfy customers and quality of the food, taste of food, freshness of the food ingredient, prompt and quick service and well communicating staff are important areas where Malaysian restaurateurs, can make improvements to generate positive behavioural intentions among Middle East tourists. Overall, this study indicates that taste of the food and environmental cleanliness are two pivotal attributes to create satisfied customers and quality of the food, taste of food and location of the restaurant are essential for positive post-dining behavioural intentions.